P15 Identifying patients who receive chemotherapy for small-cell lung cancer using large datasets. (14th November 2013) - Powell, HA; Tata, LJ; Stanley, RA; Baldwin, DR; Hubbard, RB
Abstract : Introduction: The National Lung Cancer Audit (NLCA) has collected data on primary lung cancer in England since 2004, and has now been linked with Hospital Episodes Statistics (HES) for research into inequalities in access to treatment. How well these two large datasets capture chemotherapy for small cell lung cancer (SCLC) is not known. Methods: We identified all cases of SCLC in the NLCA diagnosed between January 2004 and March 2012. We calculated the proportion of patients with a HES code for chemotherapy, and the proportion with a start date for chemotherapy in the NLCA, within 6 months of diagnosis. We inspected survival curves for people with a chemotherapy record in HES only or the NLCA only, people who had records of chemotherapy in both databases (who we could be reasonably sure had chemotherapy), and those with no record of chemotherapy. We assessed whether the results changed over time as case ascertainment in the NLCA increased from 19% to 98% between 2004 and 2009. Results: We identified 18, 398 cases of histologically confirmed SCLC; 9, 484 (52%) had chemotherapy records in both databases and 5, 100 (28%) had no record of chemotherapy in either. 737 patients (4%) had chemotherapy recorded only in HES and 2, 539 (14%) only in the NLCA. For people with a record of chemotherapy in a single database (NLCA only or HES only) survival was similar to that of people with records of chemotherapy in both datasets (Figure 1 ); the average age, stage and performance status was also very similar for people in these three groups. Survival patterns were the same when we analysed the data by year of diagnosis however the proportions with chemotherapy records in HES only or the NLCA only decreased to 3% and 12% respectively in 2011. Conclusion: Our results suggest that it is best to identify people who received chemotherapy using data in the NLCA and HES combined. A record of chemotherapy in either database appears to be a valid means of determining who received chemotherapy but if a single database is used the proportion treated is likely to be an under-estimate.